2022
DOI: 10.3389/fonc.2022.1029960
|View full text |Cite
|
Sign up to set email alerts
|

Association of inflammatory markers with survival in patients with advanced gastric cancer treated with immune checkpoint inhibitors combined with chemotherapy as first line treatment

Abstract: BackgroundThe emergence of immune checkpoint inhibitors has changed the landscape of first-line treatment of patients with advanced gastric cancer. Currently, the prognostic significance of inflammatory markers in first-line immunotherapy combined with chemotherapy for gastric cancer is currently unclear. This study aimed to identify inflammatory markers with potential to predict treatment outcome in advanced gastric cancer patients receiving immunotherapy combined with chemotherapy.MethodsThis retrospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Among these, three studies were excluded primarily due to insufficient relevant data required for survival analysis. Ultimately, this meta-analysis included six studies, encompassing a total of 815 patients ( 19 , 20 , 24 27 ) into ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, three studies were excluded primarily due to insufficient relevant data required for survival analysis. Ultimately, this meta-analysis included six studies, encompassing a total of 815 patients ( 19 , 20 , 24 27 ) into ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Extracted information included the name of the first author, publication year, country (study location), study type, sample size, patient age, study duration, treatment method, specific immune checkpoint inhibitors used, timing of detection, cut-off value, follow-up duration, and HRs (95% CIs) for OS and PFS. It should be noted that, in terms of studies that reported MLR data ( 19 , 20 ), we took the reciprocal of related HR values and corresponding confidence intervals, and exchanged the upper and lower confidence limits to convert MLR into LMR values, so as to facilitate our statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Zhang and his colleagues’ meta-analysis further corroborated these findings, integrating data and results from 17 studies, revealing that the PNI is a reliable predictive factor for gastric cancer patients receiving ICIs [ 27 ]. Meanwhile, Wan and colleagues have extensively studied inflammatory markers and found that the NLR was associated with the benefits of immunotherapy [ 28 ]. On the other hand, there is a growing awareness of the necessity to establish new biomarkers specifically for immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Having acknowledged such limitations, provided there is no medical condition that would preclude a Mediterranean-style diet with at least 20 g of fibre daily, these are not difficult interventions to counsel patients around and may carry significant potential benefit that could extend beyond ICI support [ 65 , 66 ]. Given the research above, our current pragmatic approach to supporting the gastrointestinal microbiome before and during ICI treatment makes the following recommendations within a personalised plan: Eating at least 20 g and ideally 30 g + fibre daily [ 50 ••, 66 , 67 ] within the context of a Mediterranean-style diet [ 12 ••] or other culturally appropriate plant-rich anti-inflammatory diet Minimisation/avoidance of ultra-processed foods, processed meats and sugar-sweetened drinks that have been shown to adversely impact the gastrointestinal microbiome and systemic inflammation [ 68 – 73 ], with the latter being associated with poorer ICI treatment outcomes [ 21 , 24 ] Practically this often involves switching from a Western-style diet to a more prudent Mediterranean-style dietary pattern. Avoidance of antibiotics and proton pump inhibitors (PPIs) where possible due to their impact on the gastrointestinal microbiome [ 67 , 74 76 ].…”
Section: Role Of Nutrition In Supporting Ici Treatmentmentioning
confidence: 99%
“…Minimisation/avoidance of ultra-processed foods, processed meats and sugar-sweetened drinks that have been shown to adversely impact the gastrointestinal microbiome and systemic inflammation [ 68 – 73 ], with the latter being associated with poorer ICI treatment outcomes [ 21 , 24 ] Practically this often involves switching from a Western-style diet to a more prudent Mediterranean-style dietary pattern. …”
Section: Role Of Nutrition In Supporting Ici Treatmentmentioning
confidence: 99%